Cross-tissue MiRNA profiling of extracellular vesicles and PBMCs from amyotrophic lateral sclerosis patients - Francesca Dragoni; Rosalinda Di Gerlando; Luca Diamanti; Bartolo Rizzo; Matteo Bordoni; Eveljn Scarian; Camilla Viola; Giovanni Cerchia; Susanna Zucca; Orietta Pansarasa; Stella Gagliardi (Scientific Reports)
Abstract RNA-mediated toxicity, which can be controlled by alteration of gene expression, is considered a key event in Amyotrophic Lateral Sclerosis (ALS). Transcriptomic deregulation of miRNAs expression can spread via “horizontal” RNA transfer through extracellular vesicles (EVs) to act in conjunction with proteins, leading to changes in mRNA, which can provide early signals to indicate forthcoming neuropathological changes in the brain. The aim of this work is to compare expression profiles (obtained by miRNA-seq) from different tissues to highlight commonly expressed and tissue-specific miRNAs. miRNA species from plasma EVs were correlated with miRNA profiles obtained from peripheral blood mononuclear cells (PBMCs). Each tissue from ALS patients was compared to controls, revealing 159 deregulated (DE) miRNAs in Exosomes (EXOs), 247 DE miRNAs in PBMCs and 162 DE miRNAs in Microvesicles (MVs). Next, data were filtered to include only miRNAs expressed in disease samples (not in healthy subjects), to reduce the number of tissue- and ALS- specific miRNAs (EXO n = 22, MV = 11, PBMCs n = 8). We identified specific miRNAs and pathways related to each tissue. Interestingly, in PBMCs we found mainly neuro-linked pathways, such as neurotransmitters, brain and neuron development, while in EXOs, we found miRNAs implicated in MAPK and ERB signaling. In contrast, the altered pathways in MVs were not specific. This study shows that the composition of small RNA differs significantly between blood cells and its respective EVs fraction. Differentially expressed miRNAs can target definite transcripts in different cellular and molecular fractions. It is evident that, in terms of miRNAs cargo, MVs are not specific to ALS. Therefore, future studies will focus on the interaction between cells and EXOs.